Weaving the Built Environment. Social infrastructure networks enhancing socio-spatial inclusion, urban equity and community resilience in Bogota and Medellin - Sanchez Guzman, Santiago (AESOP, 2016)
Although Bogota’s development process between 1998 and 2007 has been documented, awarded and internationally discussed mainly due to the introduction of the BRT Transmilenio system, less has been said, researched and measured about it more or less 500 Million USD primary and secondary public Schools and Libraries Infrastructure investments (mostly twice the cost of the Guggenheim Bilbao museum) carried out during this 10 years period. Thrived in a decentralized and distributive spatial pattern, the School and Libraries facilities development program is a unique example of a long run and land policy based Social Infrastructure System strategy implemented in the most vulnerable districts and intended for the poorest children of the city out of any cost for them and aimed to equilibrate social and spatial urban benefits in a traditionally highly unequal urban context. However, the success of this initiative and it urban scale positive impacts rely not only upon the quality of the facilities itself but on the articulation capacity of the projects to the existing urban fabric and the public space in the surroundings as well as to the public transportation networks. Probably the golden Lion award1 for cities won by Bogota during the 10th Biennale di Venezia in 2006 in Italy has been the most remarkable and worldwide relevant recognition for this planned and implemented urban development vision that through articulating mega projects contributed in weaving a highly fragmented urban environment, enhancing citizens accessibility to human and social resources and capitals as well as stimulating urban hope.
Proceedings of the IV World Planning Schools Congress, July 3-8th, 2016 : Global crisis, planning and challenges to spatial justice in the north and in the south